Practical Carrier of Sports Empowering Rural Revitalization: High-Quality Development of Rural Sports Events—Multiple Values and Path Exploration - Huang, Yifan (Journal of Social Science and Humanities, 2026)
Rural sports events, as a core component of rural sports, play an indispensable role in rural revitalization, building a strong sports nation, and promoting a healthy China. The research suggests that rural sports events in China have multiple values such as helping to strengthen the consciousness of the Chinese national community; driving systemic and comprehensive development of rural industries; promoting stability and sustainable development of ecosystems; and fostering a collaborative governance model involving diverse stakeholders in rural areas. However, while rural sports events move towards high-quality development, they also face challenges like inadequate event infrastructure, a shortage of professional talent supply, and insufficient integration of events. To address these issues, this paper, based on methods such as literature review, industry integration analysis, logical analysis, and case study, focuses on key problems in the high-quality development process of rural sports events and proposes targeted solutions: strengthening the dual-driving effect of policy funding guarantees and infrastructure optimization; empowering the rural revitalization talent chain through institutional reform and system optimization; and constructing a new ecological framework for the integrated development of rural sports events, aiming to provide theoretical support and practical pathways for the high-quality development of rural sports events, thus assisting in the implementation of the rural revitalization strategy.